Outdoor Temperature Influences Cold Induced Thermogenesis in Humans - Senn, Jaël R.; Maushart, Claudia I.; Gashi, Gani; Michel, Regina; Lalive d’Epinay, Murielle; Vogt, Roland; Becker, Anton S.; Müller, Julian; Baláz, Miroslav; Wolfrum, Christian; Burger, Irene A.; Betz, Matthias J. (Frontiers in Physiology, 2018)
Objective Energy expenditure (EE) increases in response to cold exposure, which is called cold induced thermogenesis (CIT). Brown adipose tissue (BAT) has been shown to contribute significantly to CIT in human adults. BAT activity and CIT are acutely influenced by ambient temperature. In the present study, we investigated the long-term effect of seasonal temperature variation on human CIT. Material and Methods We measured CIT in 56 healthy volunteers by indirect calorimetry. CIT was determined as difference between energy expenditure (EE) during warm conditions (EEwarm) and after a defined cold stimulus (EEcold). We recorded skin temperatures at eleven anatomically predefined locations, including the supraclavicular region, which is adjacent to the main human BAT depot. We analyzed the relation of EE, CIT and skin temperatures to the daily minimum, maximum and mean outdoor temperature averaged over 7 or 30 days, respectively, prior to the corresponding study visit by linear regression. Results We observed a significant inverse correlation between outdoor temperatures and EEcold and CIT, respectively, while EEwarm was not influenced. The daily maximum temperature averaged over seven days correlated best with EEcold (R2=0.123, p=0.008) and CIT (R2=0.200, p=0.0005). The mean skin temperatures before and after cold exposure were not related to outdoor temperatures. However, the difference between supraclavicular and parasternal skin temperature after cold exposure was inversely related to the average maximum temperature during the preceding seven days (R2=0.07575, p=0.0221). Conclusion CIT is significantly related to outdoor temperatures indicating dynamic adaption of thermogenesis and BAT activity to environmental stimuli in adult humans.